A PROJECT MANAGEMENT UTILITY FOR AGRICULTURAL FACILITIES AND PUBLIC HEALTH - TILEMACHOS KOLIOPOULOS (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2018)
This research study analyses the project management of agricultural facilities that protect agricultural food and public health from associated toxic hazardous landfill emissions and risks. Project management is presented by the development of a geoinformatics utility so as to improve operational management not only in food production minimizing the consumption of resources but also to improve the bio capacity development of the services and products through effective constructions minimizing risks for public health. Useful results are presented based on geoinformatics utility that develops sanitary drawings in sustainable designs minimizing risks and indoor pollution hazardous emissions in working spaces minimizing health risks.